Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1152/jn.00253.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Somatotopic Representations of Heat and Mechanical Pain in the Operculo-Insular Cortex: A High-Resolution fMRI Study

Abstract: Whereas studies of somatotopic representation of touch have been useful to distinguish multiple somatosensory areas within primary (SI) and secondary (SII) somatosensory cortex regions, no such analysis exists for the representation of pain across nociceptive modalities. Here we investigated somatotopy in the operculo-insular cortex with noxious heat and pinprick stimuli in 11 healthy subjects using high-resolution (2 × 2 × 4 mm) 3T functional magnetic resonance imaging (fMRI). Heat stimuli (delivered using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 78 publications
6
104
1
2
Order By: Relevance
“…The 'pain matrix' is also activated by non-painful stimuli (Mouraux and Iannetti, 2009). Using the same type of stimuli, we recently showed that the operculo-insular cortex, especially SII and the posterior insular cortex, are more pain specific (Oertel et al, 2011), which agrees with results using other noxious stimuli or assessments in patients suffering particular central pain syndromes (Peyron et al, 2002;Baumgartner et al, 2010;Garcia-Larrea et al, 2010). The present findings further support observations that pain stimuli are associated with complex and not only pain specific activations in the brain.…”
Section: Discussionsupporting
confidence: 89%
“…The 'pain matrix' is also activated by non-painful stimuli (Mouraux and Iannetti, 2009). Using the same type of stimuli, we recently showed that the operculo-insular cortex, especially SII and the posterior insular cortex, are more pain specific (Oertel et al, 2011), which agrees with results using other noxious stimuli or assessments in patients suffering particular central pain syndromes (Peyron et al, 2002;Baumgartner et al, 2010;Garcia-Larrea et al, 2010). The present findings further support observations that pain stimuli are associated with complex and not only pain specific activations in the brain.…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis of S2 included OP 1-4 as a single region of interest and demonstrated no distinct organization of nociceptive stimuli into hand and trunk areas, with the average most activated voxels independent of stimulation site within OP 4 (ipsilateral and contralateral). However, Baumgärtner et al [2010] provided evidence of somatotopy within OP 1 in response to nociceptive stimuli of the hand and foot. Therefore, we cannot exclude that there may be multiple somatotopic representations within the other single opercula (OP 1, 2, and 3).…”
Section: The Somatotopic Organization Of Painful Dermatomal Stimulationmentioning
confidence: 99%
“…Brain imaging studies have disclosed a network of cortical areas involved in nociceptive processing [Apkarian et al, 2005;Peyron et al, 2000], as well as demonstrated somatotopic organization of nociception in a number of these areas (e.g., primary and secondary somatosensory cortices, S1 and S2, respectively) [Baumgärtner et al, 2010;Bingel et al, 2004;Brooks et al, 2005;DaSilva et al, 2002;Xu et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has identified two regions in the operculoinsular region that are specifically involved in pain-related somatosensory processing: OP1, the most caudal area of the parietal operculum, and dpINS (19)(20)(21)(22)(23). To identify whether social rejection and physical pain coactivated these areas, we performed a priori ROI analyses on these regions (see Methods for details regarding ROI definition).…”
mentioning
confidence: 99%